In vivo effects of bempedoic acid on microdosed CYP probe drugs - Stoll, Felicitas E.; Amato, Salvatore; Burhenne, Jürgen; Blank, Antje (Frontiers in pharmacology, 2025)
BackgroundBempedoic acid (BA) is a novel oral cholesterol-lowering drug. So far, in vivo evidence on potential drug-drug interactions via the cytochrome P450 (CYP) enzymes is lacking.MethodsIn a clinical trial, we evaluated the effect of BA on microdosed probe drugs using a limited sampling strategy in healthy volunteers. The outcome measures were as follows: 1) the omeprazole AUC0-4h and hydroxylation index (HI) after a 100 µg dose to evaluate CYP2C19 activity, 2) the midazolam AUC2-4h after a 30 µg dose to evaluate CYP3A activity, and 3) the yohimbine AUC0-4h after a 50 µg dose to evaluate CYP2D6 activity. Partial areas under the curve (AUCs) were evaluated at baseline and under BA steady state. The endpoints were the geometric mean ratios (GMRs) with 95% confidence intervals (CI) of the partial AUCs.ResultsIn 15 participants, the AUC0-4h of omeprazole and its HI significantly decreased (GMR: 0.75, 90% CI: 0.66-0.85; change in HI p < 0.0001). There was no change in the AUC2-4h of midazolam (GMR: 1.18, 90% CI: 0.87-1.61) and AUC0-4h of yohimbine (GMR: 0.92, 90% CI: 0.75-1.14).ConclusionIn healthy volunteers, BA was a mild inducer of CYP2C19 and did not affect CYP3A or CYP2D6 activity.
Veröffentlicht: 08. April 2025
Gesehen am 26.09.2025